Human resources support for children of preschool age in rural area (1945-1959) - Мицик, Г. М. (Scientific notes of the pedagogical department, 2018)
Taking into account the analysis of scientific pedagogical sources, the article summarizes the views on the formation of preschool speech therapy in the period from 1945 to 1959. The data on the main tendencies of its development in the village are specified, the problems connected with the training of speech therapy staff oriented in their work to pre-school children living in rural areas are outlined. It is noted that the development of the system of preschool education institutions, as one of the organizational forms of providing speech therapy in rural areas, in the first post-war years largely depended on the decisions of the government of the country. The position of the Ministry of Education of the Ukrainian SSR was quite active in this in the 1950s. With a view of qualitative preparation of children for school the question on creation of stationary rural kindergartens was discussed. It is established that the tasks, content and methods of educational and educational work in mass kindergartens in accordance with the guidelines for all age groups have become more specific and specific. Despite the fact that they contained sections on the development of the native language, problems of a linguistic nature, basically, remained without attention of their workers. Logopedic preschool aid was not formed. Only here and there it was provided by educators of mass kindergartens and speech therapy centers, aimed at providing speech therapy to schoolchildren and children of older groups of kindergartens. Work in rural area in this direction was not conducted. It was noted that the purposeful preparation of speech therapists in the higher education system of Ukraine was not carried out. The first set of students in the specialty «Defectology. Oligophrenopedagogy and speech therapy» with the qualification of a special school teacher and speech therapist was held only in 1957–1958 school year. Preparation of defectologists of preschool institutions in Ukraine in the 50’s was not conducted and was not planned in the near future.